Neutralizing antibodies in relation to antibody-dependent cellular cytotoxicity-inducing antibodies against human immunodeficiency virus type I. - Böttiger, B (1988)
The presence of neutralizing antibodies against human immunodeficiency virus type 1 (HIV-1) was investigated in sera from 73 HIV-1 seropositive subjects at different clinical stages. Virus neutralization was measured as survival of MT-4 cells in a 6-7 day microassay. Sixty-three sera were also tested for antibodies inducing virus-specific antibody-dependent cellular cytotoxicity (ADCC). Neutralizing antibodies were found in 59% of sera tested, the positivity rate being 50% (9/17) in asymptomatic subjects, 67% (12/18) in patients with persistent generalized lymphadenopathy (PGL) and 54% (14/26) in AIDS patients (not significant differences). ADCC antibodies were present in 43% of the sera. Neutralizing antibodies and ADCC-inducing antibodies were found simultaneously in 35% (22/63) of the sera. Neutralizing antibodies alone were found in 22% (14/63) and ADCC antibodies alone in 6% (4/63) of the sera tested. Thirty-seven per cent (23/63) of the sera were negative for both types of antibodies, 62% of the sera with neutralizing antibodies also had ADCC inducing antibodies and 85% of the sera with ADCC antibodies had neutralizing antibodies. The titres of ADCC antibodies were higher than those of neutralizing antibodies. Thus, the presence of ADCC antibodies was related to the presence of neutralizing antibodies, but no correlation was found between the titres of these antibodies in sera positive for both activities.